THE USE OF TEACHING PROFICIENCY THROUGH READING AND STORYTELLING (TPRS) TO IMPROVE STUDENTS' LISTENING COMPREHENSION - Susan, Ivonne (2013)
Studi ini dilakukan untuk mengetahui apakah penggunaan Teaching Proficiency through Reading and Storytelling (TPRS) dapat meningkatkan kemampuan listening siswa serta mengeksplorasi kelebihan dan kekurangan dari penggunaan teknik tersebut. Studi ini adalah studi pre-eksperimental. Studi ini melibatkan 20 murid dari sekolah menengah pertama sebagai partisipan. Data-data studi ini diperoleh melalui: pre-tes, post-tes, dan interview terhadap sudut pandang para siswa dan guru mengenai teknik ini. Data yang telah diperoleh melelui pre-tes dan post-tes dianalisis menggunakan dependent t-test pada SPSS 18.0. Data yang telah diperoleh melelui interview dianalisis untuk memaparkan respon guru dan para murid mengenai kelebihan dan kekurangan dalam penggunaan teknik TPRS dalam proses belajar mengajar. Hasil dari studi ini yaitu t obt > t crit (20.870>0.456), T-hitung lebih besar dari T-tabel membuktikan bahwasanya nol hipotesis ditolak. Dengan kata lain, adanya perbedaan kemampuan listening siswa sebelum dan sesudah teknik ini digunakan. Guru dan siswa juga menyatakan bahwa TPRS dapat meningkatkan pemahaman listening siswa, meningkatkan penguasaan kosakata, membuat siswa lebih memahami cerita, dan membuat siswa merasanyaman dalam menjalani PBM di dalam kelas. Kata kunci: TPRS, pemahaman, pre-eksperimental, pre-tes, post-tes, dependent t-tes. Abstract This study investigates whether the use of Teaching Proficiency through Reading and Storytelling (TPRS) is able to improve students' listening comprehension and its advantages and disadvantages. It is a pre-experimental research. The study involved 20 students of a second grade of Junior High School as participants. The data were gained through pre-test, post-test, and interview which was viewed from teacher's and students' perspective. The data from pre-test and post-test were analyzed by using dependent t-test from the SPSS 18.0 program for Windows. Data attained from interview were analyzed in order to explore teacher's and students' responses towards the advantages and disadvantages of using TPRS in teaching-learning processes. The study shows that t obt > t crit (20.870>0.456), and it means that the null hypothesis was rejected. In other words, there is likely a difference in students' listening comprehension before and after the TPRS technique was done. Both teacher and students confirm that TPRS is able to improve able to improve students' listening comprehension, students' vocabulary mastery, lets the students understand more about the story, and makes the students feel comfortable in the learning process. Keyword: TPRS, comprehension, pre-experimentall, pre-test, post-test, dependent t-test.